Pemodelan dan Evaluasi Proses Bisnis Menggunakan Quality Evaluation Framework (QEF) (Studi Kasus : Radjawali Sport) - Putri Puspitasari; Aditya Rachmadi; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Radjawali Sport is a manufacture company which enganges in the field of clothing line. Radjawali Sport has consumers which spreads all over Indonesia. The large number of consumers had lad to the demand of providing the best services to the consumers. However, the services that had been given to the consumers are having some problems such as delay of production process and some complaints received from the consumers. These problems are taken as serious problems for the company. The company needs to make evaluation for improving their services. The evaluation will be done by using Quality Evaluation Framework (QEF) method. The activities inside the company will be identified by value chain method. After the activities are identified, they will be decomposed and then they will be modelled by using Business Process Model and Nation (BPMN). The result of quality factor calculation which doesn't conform to the target will be analyzed by Root Cause Analysis (RAC). RAC contains of fishbone diagram method that will be used to identify the source of the problems. The result shows that there are 7 quality factors which doesn't conform to the target. These factors are shipping duration of raw material, duration of product checking in sewing devision, sewing process, duration of product checking in embroidery division, packing, product improvement, and remanufacture. The root problem analysis found that there are 7 root problems which found in limited employees, no regular checking by the company owner, no official rules, the application of manual methods, no expert employee, supporting methods is still traditionally and no regular checking.